TGF-β blockade improves the distribution and efficacy of therapeutics in breast carcinoma by normalizing the tumor stroma - Liu, Jieqiong; Liao, Shan; Diop-Frimpong, Benjamin; Chen, Wei; Goel, Shom; Naxerova, Kamila; Ancukiewicz, Marek; Boucher, Yves; Jain, Rakesh K.; Xu, Lei (Proceedings of the National Academy of Sciences - PNAS, 2012)
Although the role of TGF-ß in tumor progression has been studied extensively, its impact on drug delivery in tumors remains far from understood. In this study, we examined the effect of TGF-ß blockade on the delivery and efficacy of conventional therapeutics and nanotherapeutics in orthotopic mammary carcinoma mouse models. We used both genetic (overexpression of sTßRII, a soluble TGF-ß type II receptor) and pharmacologie (1D11, a TGF-ß neutralizing antibody) approaches to block TGF-ß signaling. In two orthotopic mammary carcinoma models (human MDA-MB-231 and murine 4T1 cell lines), TGF-ß blockade significantly decreased tumor growth and metastasis. TGF-ß blockade also increased the recruitment and incorporation of perivascular cells into tumor blood vessels and increased the fraction of perfused vessels. Moreover, TGF-ß blockade normalized the tumor interstitial matrix by decreasing collagen I content. As a result of this vessel and interstitial matrix normalization, TGF-ß blockade improved the intratumoral penetration of both a low-molecular-weight conventional chemotherapeutic drug and a nanotherapeutic agent leading to better control of tumor growth.